Time resolved studies of femtosecond laser induced ablation from solid surfaces - Sokolowski-Tinten, K; Bialkowski, J; Cavalleri, A; von der Linde, D (1998)
Ultrafast time resolved microscopy has been used to study the dynamics of femtosecond laser induced ablation from the surfaces of various semiconductors and metals. Upon ablation initially metallic matter transforms into a transparent state with a high index of refraction.